Proyecto de factibilidad para la creación de una empresa de servicios de limpieza en el cantón Tena, Provincia De Napo, para el año 2015 - Rivadeneyra Rodríguez, Karen Daniela (2016)
This research for "Creating a Company Cleaning Services in Canton Tena, Napo Province", it was made in order to activate the local economy and encourage the development of micro, small and medium enterprises in canton. The project aims and objectives, to carry out this research, the application of various methods and techniques was necessary; the descriptive method was used to determine the problem, mathematical-analytical method provided an analysis of information obtained from surveys by data tabulation, who served in the market study and financial, among the techniques used have the technical survey, allowed to collect all the necessary information to the economically active population (EAP) and suppliers of the canton. In the market study of 13,866 potential demand, in addition to a real demand for 5,269 and 2,687 effective demand, that for the first year of life of the project it is determined. Within the technical study, the installed capacity is determined, capacity utilization and the optimal location for the company. In organizational studies, organizational structure where hierarchical levels and functions manuals include arises, the legal framework was also determined. In the financial study it found that the project requires an investment of USD $ 47,238.49 dollars of the United States of America themselves to be financed by equity of the 3 partners of the company. In the financial evaluation the Net Present Value (NPV) of the project is $ 106.324, 69; Internal Rate of Return (IRR) 12.24% and this satisfactory value for the project. The time for payback is 2 years, 11 months and 9 days. The indicator cost-benefit ratio is 1.35, meaning that for every dollar invested a profit of USD $ 0.35 $ obtained from the United States of America; positive indicators that determine that the project is financially profitable. The Environmental Impact Study was determined that the socio-economic aspect was positively affected as it will generate employment opportunities, while pollution and air quality, soil and water will be negatively influenced by the frequent use of disinfectants. After the development of studies that make the project concludes that: in Market Study found that there is unmet demand in the canton Tena.